2014
DOI: 10.4037/ccn2014442
|View full text |Cite
|
Sign up to set email alerts
|

Destination to Nowhere: A New Look at Aggressive Treatment for Heart Failure—A Case Study

Abstract: Approximately 5.7 million people in the United States experience heart failure, and about 670 000 new cases are diagnosed annually. Patients who are ineligible for heart transplant may benefit from a left ventricular assist device. These devices have provided patients with an increased life span, but eventually patients die of the underlying heart disease. This case study illustrates the appropriate use of palliative care teams to address preparedness planning and help decrease moral distress among nursing sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…28 Discussing advanced directives and advanced care planning early and throughout the illness trajectory as part of lifesaving care empowers the patient and helps make explicit to the team the patient's wishes. 29 As HF progresses, patients experience multiple symptoms and poor QOL. The symptoms include fatigue, dyspnea, pain, depression, systemic edema, insomnia, anxiety, confusion, cognitive impairment, anorexia, nausea, and constipation.…”
Section: Palliative Care For Persons Managed In a Heart Failure Centermentioning
confidence: 99%
“…28 Discussing advanced directives and advanced care planning early and throughout the illness trajectory as part of lifesaving care empowers the patient and helps make explicit to the team the patient's wishes. 29 As HF progresses, patients experience multiple symptoms and poor QOL. The symptoms include fatigue, dyspnea, pain, depression, systemic edema, insomnia, anxiety, confusion, cognitive impairment, anorexia, nausea, and constipation.…”
Section: Palliative Care For Persons Managed In a Heart Failure Centermentioning
confidence: 99%
“…25,39 Thus, the establishment of the patients' advance directives and the documented discussions that outline the conditions under which the patients desire the device to be withdrawn is critical to ensure the patients' wishes are met. [39][40][41] Discussions need to include PC and EOL care wishes relative to the VAD particularly for patients with VAD support for long periods of time or patients who are living with unpleasant symptoms caused by complications of VAD support. 38 Of 20 patients with a VAD who actively participated in VAD care preference discussions, retrospective review showed that 17 chose to actively withdraw support and three chose to wait until they lost consciousness before having the device withdrawn.…”
Section: Ventricular Assist Devicesmentioning
confidence: 99%
“…Therefore, patients need to understand the immediacy of death following VAD withdrawal, queried about the conditions under which they would desire the device be withdrawn, and the VAD care preferences should be documented to ensure the patients' wishes are met. [39][40][41]…”
Section: Ventricular Assist Devicesmentioning
confidence: 99%